Temperature modulates systemic and central actions of thyroid hormones on BAT thermogenesis - Rial-Pensado, Eva; Rivas-Limeres, Verónica; Grijota-Martínez, Carmen; Rodríguez-Díaz, Amanda; Capelli, Valentina; Barca-Mayo, Olga; Nogueiras, Rubén; Mittag, Jens; Diéguez, Carlos; López, Miguel (Frontiers in Physiology, 2022)
Thyroid hormones (THs) play a major role regulating energy balance and brown adipose tissue (BAT) thermogenesis, as well as body temperature, as shown in hyperthyroid patients. However, the current landscape of preclinical thyroid hormone models is complex. For example, while rats become catabolic after TH administration, mice gain weight; so, these differences in species need to be analyzed in detail and specially whether temperature could be a factor. Here, we aimed to investigate the effect of environmental temperature on those actions. Rats were subcutaneously treated with L-thyroxine (T4) or stereotaxically within the ventromedial nucleus of the hypothalamus (VMH) with triiodothyronine (T3) and housed at 23ºC, 4ºC or 30ºC; energy balance, BAT thermogenesis and AMP-activated protein kinase (AMPK) in the VMH were analyzed. Our data showed that the effect of both systemic T4 of central T3 on energy balance and BAT thermogenesis was dependent upon environmental temperature. This evidence is of interest in the design of experimental settings highlighting the species-specific metabolic actions of THs, and in understanding its physiological role in the adaptation to temperature.